Frequency of Multivessel Disease in Patients Presenting with Acute Myocardial Infarction - Iftikhar, Umair; Yasmin, Samra; Majeed, Uzma; Javiad, Sahrish; Saleem, Zoha; Hannan, Ayesha; Raza, Muhammad Arsalan; Arshad, Hamid (Biological and Clinical Sciences Research Journal, 2025)
Acute myocardial infarction (AMI) is a major cause of morbidity and mortality worldwide. Multivessel disease, defined as the involvement of more than one vascular bed including coronary, peripheral, and cerebrovascular circulation, significantly influences prognosis and management strategies in AMI patients. However, local data regarding its frequency remains limited. Objective: To determine the frequency of multivessel disease in patients with acute myocardial infarction. Study Design: Cross-sectional study. Place and Duration of Study: At Punjab Institute of Cardiology, Lahore, Cardiology Department from 15-01-2025 to 15-04-2025. Methodology: This cross-sectional study was conducted after taking ethical approval from the IRB of Punjab Institute of Cardiology, Lahore. This study was done on 120 patients diagnosed with AMI (STEMI and NSTEMI) after taking informed consent. Data was collected using a proforma. Demographic details of patients and frequency of multivessel disease (involvement of more than one vascular bed, including peripheral arterial disease, coronary artery disease, and cerebrovascular disease) were noted. Data analysis was completed using SPSS version 26. Results: Among 120 patients with AMI, 39% patients had coronary artery disease, 17% had peripheral arterial disease, and 9% had cerebrovascular disease. Multivessel disease was found in 13% of the study population. Multivessel disease was more common in older patients, females, those with higher BMIs, and those presenting with NSTEMI; however, none of these associations were statistically significant (p >). Conclusion: This study highlights that a significant proportion of patients with acute myocardial infarction have underlying multivessel disease, emphasizing the systemic nature of atherosclerosis. Identifying the presence of multivessel involvement is crucial, as it is associated with a higher risk of adverse cardiovascular outcomes. Early recognition and comprehensive vascular assessment in AMI patients can guide more effective management strategies and improve long-term prognosis.